Belgian endive-derived biostimulants promote shoot and root growth in vitro - Halimat Yewande Ogunsanya; Pierfrancesco Motti; Jing Li; Hoang Khai Trinh; Lin Xu; Nathalie Bernaert; Bart Van Droogenbroeck; Nino Murvanidze; Stefaan P. O. Werbrouck; Sven Mangelinckx; Aldana Ramirez; Danny Geelen (Scientific Reports, 2022)
Abstract Recovering biostimulant compounds from by-products of crops is a promising strategy to add value, enhance sustainability, and increase the environmental safety of the agricultural production chain. Here, we report consistent root and shoot growth-stimulating bioactivity present in water-based extracts from Belgian endive forced roots (Cichorium intybus var. foliosum) over two consecutive harvest years. The shoot and the primary root of in vitro cultivated Arabidopsis thaliana treated with Belgian endive extract were about 30% increased in size compared to plants grown under control conditions. The ornamental species Plectranthus esculentus also showed enhanced in vitro shoot and root growth, suggesting bioactivity on a broad range of species. Fractionation of the Belgian endive extracts into aqueous and organic subfractions coupled with bioactivity measurements showed that the principal root and shoot growth-promoting ingredients are primarily water-soluble. NMR-based characterization of the bioactive aqueous fractions revealed the presence of predominantly sugars and organic acids. Malate and sugars were abundant and common to all water fractions, suggesting these molecules contributed to the growth stimulation phenotype. The findings indicate that Belgian endive roots are a source for the development of organic waste-derived biostimulants with potential for application in tissue culture and putatively for soil-grown crop production.